Childhood in street situation: Territories, relationships and social policies - Lenta, María Malena (Revista de Psicología, 2013)
The identity construction processes, body senses and social relationships of boys and girls in street situation in the Autonomous City of Buenos Aires, Argentina, were investigated. The social policies were interrogated as the causes of social exclusion, in opposition to the right’s rhetoric. An exploratory-descriptive study was developed, with a qualitative and critical approach. The sample was composed by 15 boys, girls and adolescents. Participant observation, life story and focus groups where implemented. Reproduction of social exclusion was observed by the lack of need’s record on infancy policies, violence in social speeches and gender stereotypes.